Factors Affecting Purchase Decision in Indonesian E-Commerce Industry - Kusumawardhani, Arini; Esmeralda, Ervina; Utama, Jonathan Pria; Anggraeni, Adilla (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
E-commerce is currently popular in Indonesia and has changed the way a business is transacted. The E-commerce industry itself has become a vital part of the economy in Indonesia. Many are trying to get as many users as possible and competing with each other to be the top one with various marketing strategies, yet the strategies have not always been considered sufficient. This is quantitative research with data collection through questionnaires to the 326 respondents, but 121 respondents did not pass the filter questions and get 205 respondents for valid data. The data analysis method used in this study is Partial Least Square (PLS). The results show that price discount, advertising effectiveness, and brand awareness have a significant positive effect on purchase decisions. The results show that attractiveness has a significant positive effect on brand awareness. The results also show trustworthiness and expertise which has no significant effect on brand awareness.